Analysis of Non-Muslim Crescent Sighting Testimonies in the Book Fathul Mu'in by Sheikh Zainuddin Al-Malibary - khaeratus saadah (Abdi Masyarakat, 2026)
Crescent sighting is fundamental to determining the beginning of the Hijri month, making it crucial and requiring careful decision-making or determination, as it relates to worship. The open and public sighting process allows anyone, including non-Muslims, to witness it, necessitating clear rules for making decisions regarding crescent sighting. The research method used in this study isLiterature Research or literature research using descriptive analysis and Fazlurrahman's Double Movement theory approach. In the book Fathul Mu'in by Zainuddin al-Malibary, it is explained that news conveyed by non-Muslims regarding the crescent moon is the same as a judge's decision. Testimony regarding the crescent moon made by non-Muslims cannot be accounted for by witnesses because they do not have the power and authority over Muslims, as this relates to Islamic worship. Non-Muslims can still report and provide information regarding the presence of the crescent moon, but cannot be used as witnesses to swear an oath before a judge.